The safety and effectiveness of transforaminal lumbar interbody fusion (TLIF) surgery for the treatment of lumbar disc herniation - Wang, Wei; Guo, Zhao; Yang, Lixin; Liu, Jianning; Li, Zhiyong; Li, Jiaqi; Zhao, Hong; Sun, Tao (Frontiers in Surgery, 2025)
BackgroundThe purpose of this study is to discuss the safety and effectiveness of transforaminal lumbar interbody fusion (TLIF) for the treatment of lumbar disc herniation.MethodsFrom August 2018 to December 2021, patients with lumbar disc herniation who received TLIF treatment were included in this study. Clinical data collected during both the preoperative period and the 2-year postoperative follow-up were analyzed. The correlations between preoperative clinical indicators and postoperative functional outcomes were modeled using both univariate regression and multivariable-adjusted analyses.ResultThe study population comprised 547 consecutive cases (male: 261, 47.7%; female: 286, 52.3%). Stratified outcome analysis showed 458 patients (83.7%) attained optimal surgical recovery without detectable morbidity, contrasted with 89 cases (16.3%) manifesting postoperative complications. The univariate analysis of postoperative complications found that the recurrence of symptoms was related to body mass index (BMI), preoperative pain time, High-level segment, intraoperative bleeding volume and postoperative visual analog scale (VAS)-back. Postoperative hematoma was related to hypertension and wound drainage. Poor wound healing was related to BMI and Wound drainage volume. However, this study failed to find the related factors of wound infection. After binary logistic analysis of the above single factors, we found that BMI and preoperative pain time were independent risk factors for symptom recurrence, and BMI were independent risk factors for Poor wound healing.ConclusionTransforaminal lumbar interbody fusion surgery can safely and effectively treat lumbar disc herniation.